Relevance of Resin for Photoelasticity - Martins,Adriana Vieira (2019)
The goal of this study is to test photoelastic resins for manufacturing models with teeth and/or implants under chewing load. Four commercial brands have been chosen: Araldite (Ciba Chemicals), Flexible GIV-Rigid GIV (Polipox) and PL2 (Measurements Group). Nine discs were manufactured, four of them from each of the photoelastic resin brands and five from different proportions of mixture between Flexible GIV and Rigid GIV. All the models were subjected to the diametral compression test, and observed in a circular polariscope. The first order fringe has always been adopted as a benchmark to calculate the photoelastic constant. To the load of interest (150 Newtons), Flexible GIV resin showed areas that followed the elastic regime. Residual stresses for the resin PL2 and persistence of bubbles within the model were observed. Rigid GIV Resin generated the first fringe order only at 280 Newtons load. Araldite resin behaved within the elastic regime and there were no areas with excessive concentration of fringes. The models generated from the manual mixing generated non-homogeneous photoelastic images. The Araldite resin showed to be the most suitable material for manufacturing birefringent models with teeth and/or implants under chewing load.